Pancasila and the Long Shadow of Suharto's Authoritarianism, 1966-1998 - Nasir bin Nayan (Tanjung Malim, 2024)
Pancasila and the Long Shadow of Suharto's Authoritarianism, 1966-1998 by Nasir bin Nayan